The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2147/opth.s42468
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc size and progression of visual field damage in patients with normal-tension glaucoma

Abstract: PurposeOur goal was to evaluate the influence of optic disc size on the progression of visual field damage in patients with normal-tension glaucoma (NTG).Subjects and methodsEighty-two eyes of 82 NTG patients who had been receiving topical antiglaucoma medications and followed-up for more than 4 years were enrolled in this study. The patients were allocated to two groups, according to the mean size of their optic discs. The data were analyzed using regression analysis, based on the Cox proportional hazard mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…A single follow-up visit was conducted after three months of initial diagnosis similar to the method of Hayamizu et al [26]. Glaucoma was diagnosed according to the following characteristics:…”
Section: Methodsmentioning
confidence: 99%
“…A single follow-up visit was conducted after three months of initial diagnosis similar to the method of Hayamizu et al [26]. Glaucoma was diagnosed according to the following characteristics:…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, previously published data from this cohort of children reported that Aboriginal and Torres Strait Islander children had a thinner CCT (mean difference 9 µm) and a lower IOP (mean difference 1.3 mm Hg) compared with non-Indigenous children. 18 Given that numerous studies have shown an association between both thin CCT and larger ONHs with an increased risk of developing glaucoma in adulthood, [14][15][16][35][36][37][38][39] it is surprising that the limited available evidence suggests that Aboriginal and Torres Strait Islander adults exhibit low rates of glaucoma. 40,41 Current estimates on the prevalence of glaucoma in Aboriginal and Torres Strait Islander adults vary between 0.5% and 2.2% 6,40,41 compared with 1.8% to 3.0% among non-Indigenous Australians, 42,43 although it should be noted that the quality of evidence regarding the prevalence of glaucoma in Aboriginal and Torres Strait Islander adults is limited by variable testing protocols and lack of stringent and robust diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%